Encyclopedia of the Spanish-American & Philippine-American wars - Keenan, Jerry (ABC-CLIO, 2001)
This encyclopedia drives students and interested readers to the basic information about the Spanish-American and Philippine-American wars. Essential information like names, dates and summaries of the significant events related to those wars comprises it. To understand the conflicts, Political backgrounds of each country are presented.